AN OVERVIEW OF INDONESIAN LOANWORDS FROM FRENCH - Hardini, Tri Indri; GrangÃ©, Philippe (Indonesian Journal of Applied Linguistics, 2016)
When two languages come into contact, they exert a reciprocal influence, often unbalanced. A phenomenon that often occurs in case of language contact is the absorption or borrowing of lexical elements, which will enrich the vocabulary of the receiving language. In this article, we deal with words adopted from French in Indonesian and vice-versa. This research shows that most of the words of French origin in Indonesian/Malay language were borrowed through Dutch. Historical background explains why there are no direct loanwords from French language in Indonesian. Nowadays, a second batch of words originating from Old French finds their way into Indonesian through English. On the other hand, very few words from Malay-Indonesian origin were borrowed in French, and their route was not straight either: they were conveyed through Portuguese or Dutch. Phonological adaptation and shift of meaning may have happen when the words were loaned from French to Dutch language or later, when adapted from Dutch into Indonesian language. The data analysed in this article may help teachers of French as a Foreign Language in Indonesia, as well as teachers of Indonesian as a Foreign Language in French-speaking countries, to predict which words will be immediately recognized by their students, and when they should pay extra-attention to faux-amis (cognates whose meanings differ).